Explore the Bereavement Needs of Families of Children With Cancer From the Perspective of Health Caregivers: A Qualitative Study - Pakseresht, Maryam; Rassouli, Maryam; Rejeh, Nahid; Rostami, Shahnaz; Barasteh, Salman; Molavynejad, Shahram (Frontiers in Psychology, 2021)
Introduction: The experience of bereavement is associated with severe physical, psychological, social and spiritual reactions in the parents of children with cancer. Because of that, the families of these children need to receive bereavement services. The aim of this study was to explore the bereavement needs of families of children with cancer from the perspective of health caregiver as people who have a close relationship with the child and the family. Methods: This qualitative descriptive study design in. In total 15 semi-structured interviews were conducted using a purposive sampling in 2018. Interviews were recorded and transcribed and conventional content analysis was used to analysis the data. The Trustworthiness of the data were assessed according to the criteria of Lincoln and Guba. Results: From the data analysis, needs of the bereaved family were categorized in three dimension including “achieving peace,” “Abandoned family access to care,” and “continuing care.” The category of “achieving peace” includes spiritual and existential support, companionship with the family, contact with other bereaved families, support in passing and accepting the bereaved and continuing empathetic communication with the family, the category “Abandoned family access to care” includes the promotion of family self-control, awareness of end-of-life care to the family, and the category of “continuing care,” includes formal and informal family care and individualized care. Conclusion: It is necessary for the care team to pay special focus to family considering the needs of the family about the death of the patient and the challenges of the family bereavement period. It is recommended that members of the health care team should be trained in assessing family needs, identifying risks of adverse outcomes, continuing care, and providing resources during bereavement. The needs of the bereaved family should also be addressed in their care plan.